The Effect of Numbered Heads Together (NHT) Cooperative Learning Model Assisted by Audio Visual Media on Learning Outcomes of Elementary School Students - Mariah Al Kibtiyah; Khairil Iba (Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the effect of the learning model cooperative type Numbered Heads Together (NHT) on the mathematics learning outcomes of elementary school students. This study used a quantitative approach and method Quasi Experiment with Posttest Only Control. The research instrument used a test while the data analysis technique uses a hypothesis test with the t test formula. The results of this study proved that the type cooperative learning model Numbered Heads Together (NHT) affects mathematics learning outcomes by being proven by hypothesis testing using the t test as follows. Based on the provisions of t-count> t-table with together, results t-count 13,718 and t-table 1.999 so that the the results of this study explained the significant influence on student learning outcomes. The effect of using the cooperative learning type Numbered Heads Together (NHT) is that students are more active in asking questions when the teacher is explaining or discussing as well as increasing student interaction in the classroom and learning is not teacher centered. Teacher can use this learning model to increase students’ enthusuasm so that student learning outcomes increase.